Wetting and Spreading of Commercially Available Aqueous Surfactants on Porous Materials - Phillip Johnson; Toby Routledge; Anna Trybala; Mauro Vaccaro; Victor Starov (Colloids and Interfaces, 2019)
The wetting properties of aqueous solutions of a commercially available surfactant at various concentrations on porous media are investigated using the KRUSS DSA100 shape analyzer and the ADVANCED software to process the data. Time evolution of both the contact angle and drop base diameter at each surfactant concentration after deposition were monitored. Three different porous substrates (sponges) were examined. The sponges used were a car sponge, dish sponge and audio sponge. The sponges were investigated both dry and at different degrees of saturation, that is, the amount of water absorbed into the sponge. It was found that pure distilled water droplets deposited on the dry porous media showed non-wetting. However, if droplets of surfactant solutions were deposited, then a change to a complete wetting case was found at all surfactant concentrations used. It has been observed that for all sponges, no matter the degree of saturation, they display a minimum contact angle after which the droplet is rapidly absorbed into the porous media.